1981
DOI: 10.1038/clpt.1981.153
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen absorption and metabolism in celiac disease and Crohn's disease

Abstract: To investigate further the conflicting results in reports of drug absorption in patients with small intestinal mucosal disease, gastric emptying and the disposition of acetaminophen were assessed simultaneously in 41 subjects (13 controls, 12 patients with Crohn's disease, and 16 with celiac disease). Acetaminophen absorption as judged by plasma concentrations and gastric emptying were slower in patients with celiac disease and Crohn's disease. Total drug absorption as indicated by urinary recovery did not dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

1984
1984
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 0 publications
0
32
0
1
Order By: Relevance
“…Parsons (1977) and showed that for a dozen antibiotics absorption was modified in either direction according to the drug considered. The rate of intestinal absorption of acetaminophen is slowed but this absorption is not quantitatively decreased (Holt et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Parsons (1977) and showed that for a dozen antibiotics absorption was modified in either direction according to the drug considered. The rate of intestinal absorption of acetaminophen is slowed but this absorption is not quantitatively decreased (Holt et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Interspecies differences associated with the biliary recycling of compounds may reflect some of the differences that might occur in patients whose gall bladders have been removed. 20 Variability in gastrointestinal (GI) transit time may reflect differences that could occur in those diseases that induce GI motility changes in humans, such as Crohn's disease, 21 villus atrophy, 22 HIV infection, 23 stress, 24 and pain. 25 Therefore, improving the ability to predict species-by-formulation interactions in animal species may significantly improve our understanding of the adaptations needed to accommodate the changes in human drug absorption that may occur during medically relevant situations.…”
Section: Org) Logic Evaluation and Research (Cber) And Center Formentioning
confidence: 99%
“…Pharmacokinetic parameters such as the area under plasma concentration-time curve (AUC), the maximum plasma concentration (Cmax) and the time to maximum plasma concentration (Tmax) are derived (14,15,17). Simultaneous scintigraphy and acetaminophen emptying test have also been performed (19,20,30).…”
Section: Introductionmentioning
confidence: 99%